Novel In2S3/ZnWO4 heterojunction photocatalysts: facile synthesis and high-efficiency visible-light-driven photocatalytic activity. Issue 109 (21st October 2015) - Wang, Fangzhi; Li, Wenjun; Gu, Shaonan; Li, Hongda; Zhou, Hualei; Wu, Xiaobin
Abstract : Novel In2 S3 /ZnWO4 heterojunction photocatalysts with high-efficiency visible-light-driven photocatalytic activities were synthesized by a hydrothermal and surface-functionalized method. Abstract : Novel heterojunction photocatalysts In2 S3 /ZnWO4 were prepared by a hydrothermal and surface-functionalized method, and the optimized In2 S3 /ZnWO4 ratio was tuned to explore their visible-light photocatalytic activity for rhodamine B (RhB) degradation. The heterojunction structure formed by the In2 S3 nanoparticles grew on the primary ZnWO4 nanorods. Remarkably, In2 S3 /ZnWO4 composites exhibited much higher photocatalytic activity than that of the individual In2 S3 and ZnWO4 . The enhanced activity could be attributed to the strong visible-light absorption and the effective separation and transportance of the photogenerated charges. Moreover, the main active species for the degradation of RhB were also investigated. Then, a possible reaction mechanism for the excellent photocatalytic activity of the In2 S3 /ZnWO4 composites was proposed.